Sugammadex-induced anaphylactic reaction: A systematic review - Fatih Zecic; Mary H Smart; Taylor C Abbey; Alex Pazhempallil; Colin Korban (Wolters Kluwer Medknow Publications, 2022)
Perioperative anaphylaxis is a rare, but life-threatening hypersensitivity reaction for patients undergoing surgical procedures. Sugammadex is a relatively new drug used to reverse the neuromuscular blockade of specific anesthetics in surgery. Several case reports indicate that there may be a risk of anaphylaxis associated with the use of sugammadex This review examines the literature in order to evaluate the strength of the association between sugammadex use and anaphylaxis. A query of PubMed, EMBASE, and Web of Science was conducted using a combination of terms to identify relevant articles from inception until March 9, 2020. We included any primary study that identified sugammadex as a probable causative agent based on the World Allergy Organization diagnostic criteria for anaphylaxis. A total of 24 articles were reviewed. Across the three randomized controlled trials, there were only four cases of anaphylaxis identified. Incidence of anaphylaxis was reported in only one trial at 0.33%. Two retrospective observational studies conducted in Japan identified cases of anaphylaxis, with incidences of 0.02 and 0.04%. Among 19 case reports and series, 25 patient cases of anaphylaxis were confirmed via allergy testing to be caused by sugammadex or sugammadex-rocuronium complex. Commonly reported symptoms included hypotension, erythema, and decreased oxygen saturation. Based on the findings of this review, there appears to be a rare, but serious, association of sugammadex-induced perioperative anaphylaxis with an incidence between 0.02 and 0.04% in observational studies. It is unclear whether sugammadex on its own or in complex with rocuronium triggers this reaction, but it is clearly involved in inducing anaphylaxis. Further population studies are needed to get a more accurate global incidence rate, and more detailed allergy testing is required to better describe which step of the sugammadex reversal pathway initiates the anaphylactic attack.